Analisis Customer Relationship Management (CRM) Pada PT. Telkom Indonesia, Tbk Medan - Putri Rahmadany; Zainarti Zainarti (LPPM Universitas Labuhanbatu, 2021)
PT. Telkom is one of the telecommunications service providers in Indonesia. The BGES unit is a unit that works in the field of marketing. The BGES unit serves Corporate customers to meet the customer's internet service needs. The success of a company is measured by the level of customer satisfaction. CRM is the company's ability to maximize customer value on an ongoing basis by allocating resources more effectively focused on potential customers which in turn can increase revenue, profitability and company value. Customer Relationship Management (CRM) is able to influence the customer's desire to be able to develop true relationships, because the convenience obtained through good and efficient relationships between companies and consumers will create a long-lasting approach.